2001
DOI: 10.1016/s0960-9822(01)00316-5
|View full text |Cite
|
Sign up to set email alerts
|

The survival of motor neurons (SMN) protein interacts with the snoRNP proteins fibrillarin and GAR1

Abstract: These findings identify fibrillarin and GAR1 as novel interactors of SMN and suggest a function for the SMN complex in the assembly and metabolism of snoRNPs. We propose that the SMN complex performs functions necessary for the biogenesis and function of diverse ribonucleoprotein complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
164
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(172 citation statements)
references
References 57 publications
(2 reference statements)
8
164
0
Order By: Relevance
“…Blocking of the central interaction domain of SMN, the Tudor domain, prevents binding of small nuclear ribonucleoprotein particle core factors (Sm proteins) and abolishes assembly of small nuclear ribonucleoprotein. Deletion of 27 residues from the N terminus of SMN leads to inhibition of small nuclear ribonucleoprotein assembly, splicing, and transcription (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Blocking of the central interaction domain of SMN, the Tudor domain, prevents binding of small nuclear ribonucleoprotein particle core factors (Sm proteins) and abolishes assembly of small nuclear ribonucleoprotein. Deletion of 27 residues from the N terminus of SMN leads to inhibition of small nuclear ribonucleoprotein assembly, splicing, and transcription (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro binding assays performed with full-length and truncated forms of the protein showed that SMN interacts directly with both fibrillarin and GAR1 and that the interactions are mediated by the RG-rich domains of fibrillarin and GAR1. Co-immunoprecipitation experiments demonstrated that the SMN complex interacts with fibrillarin and GAR1 in vivo in human cells (Pellizzoni et al 2001a). Furthermore, overexpression of a dominant-negative mutant of SMN, SMNΔN27, causes a massive reorganization of snoRNPs, pointing again to a functional interaction between snoRNPs and the SMN complex in vivo.…”
Section: A Role For the Smn Complex In The Biogenesis Of Other Rnpsmentioning
confidence: 96%
“…SMN also binds directly to fibrillarin and GAR1, constituents of box C/D and box H/ACA small nucleolar RNPs (snoRNPs), respectively (Jones et al 2001;Pellizzoni et al 2001a). In vitro binding assays performed with full-length and truncated forms of the protein showed that SMN interacts directly with both fibrillarin and GAR1 and that the interactions are mediated by the RG-rich domains of fibrillarin and GAR1.…”
Section: A Role For the Smn Complex In The Biogenesis Of Other Rnpsmentioning
confidence: 99%
“…Previous studies have provided evidence that the SMN complex functions in the assembly of spliceosomal snRNPs, pre-mRNA splicing, and transcription (16, 20, 24 -26). The SMN complex may also play a role in the metabolism of snoRNPs involved in processing and modification of ribosomal RNA (18,19).Although the molecular mechanisms of SMN function are not yet known, these findings have led to the proposal that the SMN complex is a macromolecular machine, which functions in the assembly and function of several RNP complexes (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Understanding the function of the SMN complex at the molecular level is necessary to uncover the defect responsible for SMA.…”
mentioning
confidence: 99%